Heteroleptic iron(iii) Schiff base spin crossover complexes: halogen substitution, solvent loss and crystallite size effects. Issue 21 (17th May 2017) - Phonsri, Wasinee; Macedo, David S.; Davies, Casey G.; Jameson, Guy N. L.; Moubaraki, Boujemaa; Murray, Keith S.
Abstract : New heteroleptic iron(iii ) spin crossover complexes, [Fe(qsal-X)(thsa)]· n MeCN, have been investigated. Halogen substitution, solvent and crystallite size effects are discussed. Abstract : The influence of the halogen substituent on the qsal moiety of iron(iii ) heteroleptic compounds with the formulae [Fe(qsal-X)(thsa)]· n MeCN, where qsal-X − = X-substituted quinolylsalicylaldimine; thsa 2− = thiosemicarbazone-salicylaldiminate; X = F; n = 2.5, 1·2.5MeCN and X = Cl2, Br3 and I4, n = 1 (labelled2·MeCN, 3·MeCN and4·MeCN, respectively) has been systematically investigated. Magnetic studies on solid samples show incomplete spin crossover in1–3 which can be related to MeCN solvent loss. Complex4·MeCN remains fully LS up to 360 K. Single crystals have been examined at variable temperatures for samples possessing different degrees of solvation. Intermolecular C–X⋯H interactions are present for X = F, Cl and Br while a C–I⋯π interaction is uniquely observed in4·MeCN . These preferential interactions result in different supramolecular packings of the various halogen substituted compounds. However, as the LS stability increases from F to I, the ligand field strength is then also suggested to increase from F to I. Consequently, in this family, the electronic structure resulting from halogen variation is believed to influence the magnetic properties more than crystal packing effects. Mössbauer spectra, at variable temperatures, confirm the presence of Fe(iii ) and the magnetic properties in these compounds. The effect of different drying methods as well as the crystal/powder effect on the magnetic properties are discussed in the case of2·MeCN .